Implementation of the Independent Curriculum in Mobilizing Schools - Vivina Eprillison Eprillison; Stevani Stevani; Jimi Ronald; Mona Amelia; Jolianis Jolianis (Universitas PGRI Sumatera Barat, 2023)
The implementation of the Merdeka Curriculum seeks to restore learning in order to realize the transformation of education in Indonesia for the better. Merdeka Belajar is a breakthrough policy rolled out by the Minister of Education which aims to return education management authority to schools and local governments. This decision was made in order to recover learning loss that occurs under special conditions. Therefore, education units or groups of education units need to develop curricula with the principle of diversification in accordance with the conditions of education units, regional potential, and students. In the Merdeka Curriculum, teachers can recognize students' potential more deeply in order to create relevant learning. Related to this, there are still some teachers who are still unfamiliar with the implementation of this curriculum. So that UPGRISBA lecturers pioneered community service activities on how to implement this independent curriculum in mobilizing schools, especially in choosing learning media that are in accordan80ce with curriculum demands, and this activity is packaged in the form of bimtek. The method in this activity is through socialization and delivery of material. The service team explained thoroughly about Merdeka Belajar, providing assistance in compiling and mapping the curriculum. The result of this service is to increase the knowledge and understanding of teachers and schools in developing this curriculum. Keywords: Implementation; Independent Curriculum; Mobilizing School; Learning Media